Microaggression and Implicit Bias. Issue 11 (November 2021) - Turner, Jacquelyn; Higgins, Robert; Childs, Ed
Microaggression is an unconscious statement or action regarded as discrimination against a marginalized community. Microaggression coupled with implicit bias (unconscious prejudice in favor or against one person or group) can be psychologically damaging to the targeted community. The difficulty with microaggressions and implicit biases is that they are subjective and unconscious, and the offender may not view them as damaging. Microaggressions and implicit biases can affect both the patient and the physician. Whether it is the patient that is the victim of these phenomena or the physician, the goal of quality patient care is adversely affected. When patients are victims, bias can also lead to systematic dismissal of symptoms, inferior medical services, and less aggressive preventive care. Physicians who are victims of such phenomena may deal with the repeated trauma of receiving microaggressions and biases from patients and/or colleagues which may cause mental distress and ultimately functional impairment affecting work performance. In either case, repeated direct and indirect exposure of microaggressions and biases through encounters within and outside the workforce are cumulative leading to lasting internalized damage. Awareness that implicit biases and microaggressions exist and recognition that these phenomena are problematic are the first steps toward fostering a more equitable and inclusive culture. As a society and especially as health care workers, we must become increasingly culturally aware and sensitive of all communities for the ultimate good of patient care.